Assessing roof retrofit cooling potential under synergistic climate–urbanization impacts in Wuhan: An integrated WRF-based framework using PLUS-predicted LCZs - Xilin Zhou; Shuangjiang Peng; Zhengyuan Xu; Shuting Yan (Sustainable Cities and Society, 2026)

Enabling fast Li+ transport in cellulose nanocrystals polymer electrolytes via grafting flexible acrylates for stable solid-state lithium metal batteries - Xinyan Lv; Shuting Liu; Lin Peng; Sheng Liu; Zhenkun Liu; Zuyun Chen; Xiaoyuan Yu (Carbohydrate Polymers, 2026)

Diverse crop rotation promoted crop yield via microbial networks in North China Plain - Shuting Yu; Yubin Zhao; Tianshu Wang; Shuihong Yao; Yang Gao; Jun Li; Xinhua Peng; Bin Zhang (European Journal of Agronomy, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

pH/temperature dual-responsive antifungal delivery system based on polydopamine-modified montmorillonite for sustained essential oil release - Guixiang Teng; Hongyu Wang; Shuting Zhang; Mengyuan Yu; Yanzan Meng; Meng Zhao; Yan Yang; Peng Pu; Chun Zhang (Applied Clay Science, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

Structural controls of the Shawn gold system, Siguiri district, West Africa: Integrating tectonics, deep drilling and microstructural analysis - Kai Zhang; Shuyun Cao; Yibin Peng; Shuting Wang; Xiaowen Li; Lefan Zhan; Jing Guo (Journal of Structural Geology, 2026)

Aniline Degradation via 2‐Aminophenol: Genetic Basis, Broadened Players and Interspecies Cooperation - Shuting Xu; Peng Liu; Ling Zheng; Na Liu; Huihui Zhao; Yongguang Jiang (Environmental Microbiology, 2026)
For more than four decades, the catechol route has been the only genetically resolved aerobic pathway for aniline biodegradation. The genetic basis of aniline degradation via 2‐aminophenol is relatively unexplored. In this study, Pseudomonas sp. ANNB1 degraded aniline aerobically with trace accumulation of 2‐aminophenol, phenylhydroxylamine, nitrosobenzene and nitrobenzene. The ANNB1 genome encodes a dmp gene cluster and two nbz operons, consistent with the degradation ability of this strain towards phenol and 2‐aminophenol. During aniline degradation, the transcription levels of both dmp and nbz genes were significantly elevated. Deletion of nbzCaCb caused 2‐aminophenol accumulation and a 79.5% reduction in aniline removal, whereas loss of dmpMNOP abolished aniline degradation. Compared to previously characterised aniline‐degradative gene clusters, the dmp operon has a broader phylogenetic distribution. Moreover, co‐cultures of phenol‐ and 2‐aminophenol‐degraders showed synergistic aniline degradation in the presence of additional carbon and nitrogen sources. In conclusion, phenol hydroxylase can initiate aniline degradation by catalysing it to 2‐aminophenol. Furthermore, this work provides a genetic framework for engineering synthetic consortia targeting multiple pollutants.

Myasthenia Gravis patients have reduced DTI-ALPS-Index and gBOLD-CSF coupling, suggesting impaired brain waste clearance - Jianxian Zeng; Shuting Han; Mengying Zhu; Yi Shang; Peng Wu; Qinghua Gu; Yonggang Li (Brain Imaging and Behavior, 2026)

Entropy-Infused soft Sensing: A standpipe pressure feature modeling approach for Solid-Phase mass flux measurement in fluid catalytic cracking units - Lihua Huang; Zitong Zhang; Shuting Wan; Wei Peng; Jiafu Zhang; Zhonglin Ma; Mingxin Zhang (Fuel, 2026)

Long-term assessment of natural mineral-based electrochemical systems for concurrent wastewater treatment and nutrient recovery - Yukun Xing; Shuting Chen; Baile Wu; Xiyuan Feng; Ke Hu; Xiaoxiang Zhang; Junyu Zhou; Jingsheng Shi; Yafei He; Peng Li; Zhengyu Jin (Journal of Water Process Engineering, 2026)

Effects of sulfamethoxazole stress on pollutant removal performance of unsaturated constructed wetlands - Yuechang Wang; Linlan Zhuang; Yuanjun Su; Shuang Liu; Zhen Hu; Jian Zhang; Xiaoping Wang; Shaoming Cui; Gang Peng; Shuting Xie (Journal of Environmental Sciences, 2026)

Genetic evidence does not support causal associations between brain structures and fall risk: evidence from Mendelian randomization - Gengxin Dong; Shuting Peng; Qi Gao; Dapeng Bao (Brain Imaging and Behavior, 2026)

Laboratory-scale characteristics of micro-slip during fault quiescence and implications for injection-induced reactivation stability - Ning Yang; Peng-Zhi Pan; Shuting Miao; Wenbo Hou (International Journal of Rock Mechanics and Mining Sciences, 2026)

High pressure torsion technology applied to ZnO nanomaterials for enhancing the room-temperature HCl sensing performance - Shuting Wei; Dan Yang; Renquan Guan; Peng Xu; Yuxin Wang; Yingmin Teng; Aicen Li; Junkai Zhang; Huaqiao Tan; Lili Wang; Zheng Lou; Wenjuan Zhang; et al. (Chemical Engineering Journal, 2025)

A comprehensive analysis of stroke risk factors and development of a predictive model using machine learning approaches - Songquan Xie; Shuting Peng; Long Zhao; Binbin Yang; Yukun Qu; Xiaoping Tang (Molecular Genetics and Genomics, 2025)

FAK mediates mechanical signaling to maintain epithelial homeostasis through YAP/TAZ-TEADs - Yang Peng; Qiuyun Yuan; Shuting Zhou; Jianguo Gan; Zhengzhong Shen; Xiaoqiang Xia; Yuchen Jiang; Qianming Chen; Yao Yuan; Gu He; Qiang Wei; Xiaodong Feng (Histochemistry and Cell Biology, 2025)

Electrospun polyvinyl alcohol/chitosan-ZIF-8@cyanidin cation-gallic acid multifunctional nanofilm for real-time visual monitoring of beef freshness - Qian Liang; Maonan Xu; Yalan Peng; Junwen Huang; Minjian Liao; Dongsong Lin; Yongkai Chen; Wuyi Zhou; Wenxu Zheng; Xianming Dong; Shuting Zhang (Chemical Engineering Journal, 2025)

Performance of different corn hybrids and their corresponding water consumption analysis under various water management practices: Insights from experiments conducted under rain-shelters based on the TOPSIS method - Lei Wang; Jing Chen; Zhenyu Chu; Baizhao Ren; Bin Zhao; Peng Liu; Shuting Dong; Jiwang Zhang (European Journal of Agronomy, 2025)

A high-performance wearable microneedle sensor based on CNT/CCNT@Cu-ZIF-67 composites for simultaneous detection of uric acid and dopamine - Jiachen Zhu; Weiliang Wang; Luwen Wang; SongYa Cui; Dongxue Han; Shuting Liu; Shaopeng Ma; Shangbin Xi; Wei Cai; Liang Peng (Chemical Engineering Journal, 2025)

Construction of a co-culture system of Bacillus aryabhattai and Desmodesmus sp. and its performance in treating simulated wastewater with high nitrogen and phosphorus - Jianmei Dong; Shuting Peng; Xiaoyun Zhang; Zijian Xie; Ruirui Meng; Yuqin Xi; Weibao Kong (Algal Research, 2025)

Corrigendum to “Hydroxypropyl chitosan/ε-poly-L-lysine based injectable and self-healing hydrogels with antimicrobial and hemostatic activity for wound repair” [Carbohydrate Polymers 337 (2024) 122135] - Shuting Peng; Sen Niu; Qin Gao; Ruiyuan Song; Zhengxiao Wang; Ziyun Luo; Xi Zhang; Xiaofei Qin (Carbohydrate Polymers, 2025)

Konjac glucomannan/xanthan gum hydrogels loaded with metal-phenolic networks encapsulated probiotic to promote infected wound healing - Qingxin Wu; Zhengfeng Lu; Lantao Wang; Shuting Peng; Zhengxiao Wang; Yan Qiu; Zhengping Liao; Yarong Wang; Xiaofei Qin (Carbohydrate Polymers, 2025)

Effects of temperature on the physicochemical properties and volatile profiles of ‘Shine Muscat’ grape during postharvest storage - Zhenghui Jiang; Xujiao Li; Shuting Peng; Xiaobei Li; Changyan Zhou; Xiaoyan Zhao (Food Chemistry, 2025)

Enhanced antioxidant potential of In vitro gastrointestinal digestion products derived from abalone myofibrillar protein-glucose conjugates based on structural changes - Gengxin Hao; Yanwen Ma; A.YiJiang Akemujiang; Yanping Bai; Peng Ye; Xujian Qiu; Shuting Lin (Food Bioscience, 2025)

Self-cleaning micro/nano graded porous groove structure fiber membranes by coaxial spinning for purification of dye wastewater - Wanwan Peng; Shuting Tian; Shuangshuang Li; Jingcheng Wu; Daqing Wu; Peng Zhou; Hongjie Li; Yi He; Yang Bai (Environmental Research, 2025)

Energy, environmental footprints and economic benefit of substituting inorganic fertilizer with organic manure for winter wheat in Huanghuaihai Plain - Lei Wang; Jianjie Bi; Jing Chen; Baizhao Ren; Bin Zhao; Peng Liu; Shubo Gu; Shuting Dong; Jiwang Zhang (European Journal of Agronomy, 2025)

Hydroxypropyl chitosan/ε-poly-l-lysine based injectable and self-healing hydrogels with antimicrobial and hemostatic activity for wound repair - Shuting Peng; Sen Niu; Qin Gao; Ruiyuan Song; Zhengxiao Wang; Ziyun Luo; Xi Zhang; Xiaofei Qin (Carbohydrate Polymers, 2024)

Laboratory Shear Behavior of Tensile- and Shear-Induced Fractures in Sandstone: Insights from Acoustic Emission - Shuting Miao; Peng-Zhi Pan; Arno Zang; Chuanqing Zhang; Hannes Hofmann; Yinlin Ji (Rock Mechanics and Rock Engineering, 2024)

Dynamic coupling between cementation and porosity evolution of the Chang 8 tight sandstone reservoir, Ordos Basin: Insights from in-situ microanalysis - Ruiliang Guo; Weiwei Yang; Xiuqin Deng; Shuting Shi; Shutong Li; Junli Qiu; Jiaqiang Zhang; Junlin Chen; Lewei Hao; Xiaofeng Ma; Dongxu Ma; Peng Liu (Marine and Petroleum Geology, 2024)

Assessing the thermal risks for residents and visitors in traditional Street-facing Dwellings with Eaves Gallery during an extreme heatwave event - Shuting Yan; Jing He; Shuangjiang Peng; Zehua Fang; Xilin Zhou (Building and Environment, 2024)

A facile method to construct ZIF-8 MOFs on contact lens for high antibiotics loading and self-defensive release - Yi Shao; Hao Suo; Shuting Wang; Yaou Peng; Xiaoying Chu; Ziyue Long; Kanghui Du; Lili Su; Xinyue Sun; Xinyi Wang; Qingying Wang; Renlong Li; et al. (Chemical Engineering Journal, 2024)

Effects of sodium acetate and ammonium acetate on the growth and production of cellular components of Chlorella vulgaris 31 - Shuting Peng; Yueqin Cao; Zijian Xie; Xiaoyun Zhang; Saimai Ma; Weibao Kong (Journal of Applied Phycology, 2024)

Mechanism Interpretation of Sub-critical Crack Growth in Beishan Granite Subjected to Cyclic Loading - Shuting Miao; Peng-Zhi Pan; Zhaofeng Wang; Yujie Feng; Qingsong Zheng (Rock Mechanics and Rock Engineering, 2023)

Medium-chain triglyceride-stabilized docetaxel-loaded HSA nanoparticles effectively inhibited metastatic non-small cell lung cancer - Yunlong Cheng; Xiaoying Pang; Jing Wu; Lingling Zhou; Jinxu Cao; Liuchang Wang; Kang Qian; Peng Yang; Minjun Xu; Dongyu Sheng; Ran Meng; Pengzhen Wang; et al. (Drug Delivery and Translational Research, 2023)

N-methylpiperazine-diepoxyovatodiolide ameliorates peritoneal fibrosis via suppressing TGF-β/Smad and JAK/STAT signaling pathway - Min Mo; Yao Zeng; Yiqun Zeng; Shuting Li; Xiaoyang He; Xiaowen Chen; Qimei Luo; Mi Liu; Congwei Luo; Xianrui Dou; Fenfen Peng; Haibo Long (Chemico-Biological Interactions, 2023)

Effects of six phytohormones on the growth behavior and cellular biochemical components of Chlorella vulgaris 31 - Zijian Xie; Saimai Ma; Yueqin Cao; Shuting Peng; Xiaoyun Zhang; Weibao Kong (Journal of Applied Phycology, 2023)

Experimental investigation of damage evolution and fracture mechanism in rocks with a single flaw under stepwise cyclic compression - Shuting Miao; Peng-Zhi Pan; Amin Hekmatnejad; Yuxin Li (Bulletin of Engineering Geology and the Environment, 2023)

Biosynthesis of protein-based drugs using eukaryotic microalgae - Zijian Xie; Jiaxin He; Shuting Peng; Xiaoyun Zhang; Weibao Kong (Algal Research, 2023)

One-pot fabrication of SF-DA@PVDF membrane for dye adsorption and oil-in-water emulsion separation - Peng Zhou; Shihong Zhang; Yi He; Jingcheng Wu; Liang Zhou; Xiangying Yin; Shuting Tian; Shuangshuang Li; Wen Chen (Journal of Environmental Chemical Engineering, 2023)

Correction to: Root anatomical phenotypes related to growth under low nitrogen availability in maize (Zea mays L.) hybrids - Xucun Jia; Guangjun Wu; Christopher Strock; Liang Li; Shuting Dong; Jiwang Zhang; Bin Zhao; Jonathan P. Lynch; Peng Liu (Plant and Soil, 2022)

Fracture Behaviour of Two Microstructurally Different Rocks Exposed to High Static Stress and Cyclic Disturbances - Shuting Miao; Peng-Zhi Pan; Peiyang Yu; Wenbo Hou (Rock Mechanics and Rock Engineering, 2022)

Identification of nafamostat mesylate as a selective stimulator of NK cell IFN-γ production via metabolism-related compound library screening - Qinglan Yang; Shuju Zhang; Shuting Wu; Baige Yao; Lili Wang; Yana Li; Hongyan Peng; Minghui Huang; Qinghua Bi; Peiwen Xiong; Liping Li; Yafei Deng; et al. (Immunologic Research, 2022)
Natural killer (NK) cells play important roles in controlling virus-infected and malignant cells. The identification of new molecules that can activate NK cells may effectively improve the antiviral and antitumour activities of these cells. In this study, by using a commercially available metabolism-related compound library, we initially screened the capacity of compounds to activate NK cells by determining the ratio of interferon-gamma (IFN-γ) + NK cells by flow cytometry after the incubation of peripheral blood mononuclear cells (PBMCs) with IL-12 or IL-15 for 18 h. Our data showed that eight compounds (nafamostat mesylate (NM), loganin, fluvastatin sodium, atorvastatin calcium, lovastatin, simvastatin, rosuvastatin calcium, and pitavastatin calcium) and three compounds (NM, elesclomol, and simvastatin) increased the proportions of NK cells and CD3 + T cells that expressed IFN-γ among PBMCs cultured with IL-12 and IL-15, respectively. When incubated with enriched NK cells (purity ≥ 80.0%), only NM enhanced NK cell IFN-γ production in the presence of IL-12 or IL-15. When incubated with purified NK cells (purity ≥ 99.0%), NM promoted NK cell IFN-γ secretion in the presence or absence of IL-18. However, NM showed no effect on NK cell cytotoxicity. Collectively, our study identifies NM as a selective stimulator of IFN-γ production by NK cells, providing a new strategy for the prevention and treatment of infection or cancer in select populations.

Root anatomical phenotypes related to growth under low nitrogen availability in maize (Zea mays L.) hybrids - Xucun Jia; Guangjun Wu; Christopher Strock; Liang Li; Shuting Dong; Jiwang Zhang; Bin Zhao; Jonathan P. Lynch; Peng Liu (Plant and Soil, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

A New DIC-Based Method to Identify the Crack Mechanism and Applications in Fracture Analysis of Red Sandstone Containing a Single Flaw - Shuting Miao; Peng-Zhi Pan; Shankun Zhao; Jun Han; Petr Konicek (Rock Mechanics and Rock Engineering, 2021)

Long-term impact of ambient air pollution on preterm birth in Xuzhou, China: a time series study - Sha Li; Lei Peng; Xiaochang Wu; Geng Xu; Peng Cheng; Jingwen Hao; Zhaohui Huang; Meng Xu; Shuting Chen; Chao Zhang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Experimental Study on Damage and Fracture Characteristics of Beishan Granite Subjected to High-temperature Treatment with DIC and AE Techniques - Shuting Miao; Peng-Zhi Pan; Xingguang Zhao; Changyue Shao; Peiyang Yu (Rock Mechanics and Rock Engineering, 2021)

The Influence of Infilling Conditions on Flaw Surface Relative Displacement Induced Cracking Behavior in Hard Rock - Peng-Zhi Pan; Shuting Miao; Quan Jiang; Zhenhua Wu; Changyue Shao (Rock Mechanics and Rock Engineering, 2020)

Characteristics and health risk assessments of heavy metals in PM2.5 in Taiyuan and Yuci college town, China - Xiaofeng Liu; Zhilei Wang; Huiling Bai; Shuting Zhang; Ling Mu; Lin Peng (Air Quality, Atmosphere & Health, 2020)

Combined application of organic and inorganic fertilizers mitigates ammonia and nitrous oxide emissions in a maize field - Qinglong Yang; Peng Liu; Shuting Dong; Jiwang Zhang; Bin Zhao (Nutrient Cycling in Agroecosystems, 2020)

The combined application of organic and inorganic fertilizers increases soil organic matter and improves soil microenvironment in wheat-maize field - Qinglong Yang; Fengxia Zheng; Xucun Jia; Peng Liu; Shuting Dong; Jiwang Zhang; Bin Zhao (Journal of Soils and Sediments, 2020)

Effects of fertilizer type and rate on summer maize grain yield and ammonia volatilization loss in northern China - Qinglong Yang; Peng Liu; Shuting Dong; Jiwang Zhang; Bin Zhao (Journal of Soils and Sediments, 2019)

Dimethylaminomicheliolide ameliorates peritoneal fibrosis through the activation of autophagy - Shuting Li; Fenfen Peng; Wangqiu Gong; Jiayu Wu; Yuxian Wang; Zhaozhong Xu; Wenting Liu; Hongyu Li; Bohui Yin; Ying Zhang; Sijia Chen; Congwei Luo; et al. (Journal of Molecular Medicine, 2019)

Grain development and endogenous hormones in summer maize (Zea mays L.) submitted to different light conditions - Jia Gao; Jianguo Shi; Shuting Dong; Peng Liu; Bin Zhao; Jiwang Zhang (International Journal of Biometeorology, 2018)

Interactive effects of water and controlled release urea on nitrogen metabolism, accumulation, translocation, and yield in summer maize - Guanghao Li; Bin Zhao; Shuting Dong; Jiwang Zhang; Peng Liu; Tony J. Vyn (The Science of Nature, 2017)

Regulations of 6-Benzyladenine (6-BA) on Leaf Ultrastructure and Photosynthetic Characteristics of Waterlogged Summer Maize - Baizhao Ren; Jiwang Zhang; Shuting Dong; Peng Liu; Bin Zhao (Journal of Plant Growth Regulation, 2017)

Effects of plant density on the photosynthetic and chloroplast characteristics of maize under high-yielding conditions - Baizhao Ren; Wei Liu; Jiwang Zhang; Shuting Dong; Peng Liu; Bin Zhao (The Science of Nature, 2017)

Effects of shading on the photosynthetic characteristics and mesophyll cell ultrastructure of summer maize - Baizhao Ren; Haiyan Cui; James J. Camberato; Shuting Dong; Peng Liu; Bin Zhao; Jiwang Zhang (The Science of Nature, 2016)

Factors affecting summer maize yield under climate change in Shandong Province in the Huanghuaihai Region of China - Guoqing Chen; Hongjun Liu; Jiwang Zhang; Peng Liu; Shuting Dong (International Journal of Biometeorology, 2012)